Preparation and Photoreduction CO2 Activity of Phthalocyanine Modified Titania Catalysts - Fan, Jimin; Zhao, Zhihuan; Zhu, Lixiao; Wang, Zhizhong (Asian Journal of Chemistry, 2014)
Titania was modified by macrocyclic complexes using a new in situ chemical synthesis strategy. Metal phthalocyanine (MPc) was synthesized during TiO2 gel synthesis and nanocatalyst MPc-TiO2 with particle size of less than 15 nm was obtained as well. The catalysts were characterized by UV-VIS, DRS, FT-IR and XRD to verify the loading of metal phthalocyanine. The dopping of metal phthalocyanine narrowed the band-gap of TiO2 and it was responsive to visible light irradiation, the as synthesized CoPc-TiO2 heated at 300 ºC showed band gap energy of 1.84 eV. The as-prepared MPc-TiO2 catalyst can be applied in the photocatalytic reduction of CO2 under visible light, giving the yield of formic acid of 2863.3 μmol/g-catal. after 10 h of reaction. The photosensitivity of CoPc and ZnPc were better than that of NiPc. The electron density of cobalt was higher so it was beneficial to the election transformation from excited CoPc to the conduction band of TiO2. The photo-efficiency is greatly increased.